A Conceptual Model‐Based Systems Engineering Method for Creating Secure Cyber‐Physical Systems. (13th September 2022) - Larsen, Martin H.; Muller, Gerrit; Kokkula, Satyanarayana
Abstract: The Air Traffic Control industry is being increasingly exposed to rising levels of risk, as criminals and cyber‐attackers look to exploit system vulnerabilities. Air Navigation Service Providers become more demanding regarding cybersecurity concerns in the products they acquire. Consequently, systems engineers need to consider cyber security concerns early in their system's development life cycle. Model‐Based Systems Engineering methodologies are widely used to manage complex engineering projects in terms of system requirements, design, analysis, verification, and validation activities, leaving cyber security aspects aside. This paper presents a conceptual solution of a model‐based security method that aims to enable systems engineers to perform threat modeling analysis of cyber‐physical systems early and incorporate mitigation strategies into the system design, thereby reducing the cyber‐physical system's overall security‐related risks. Based on a real‐life case study the method will be validated later during execution period from Jan. – May 2022.